Vestigio trinitario en los Evangelios sinópticos - Santodomingo Orozco, Roberto Carlos (Revista Albertus Magnus, 2022)
This article addresses the relationship that exists between each synoptic gospel with a specific Person of the Holy Trinity: Matthew with the Father, Mark with the Son, and Luke with the Holy Spirit. Through the comparison of parallel texts, complemented with the analysis of other specific aspects of each gospel, it is shown that each synoptic gospel presents a special emphasis on a different Divine Person, showing how the Holy Spirit wanted to leave three gospels very similar in terms of to content, but each with a particular focus. In addition, it is evident that the order with which Tradition has always placed these three Gospels in the Bible, agrees with the order of the Trinitarian Persons.